Evaluation of mucin histochemistry in benign and malignant prostatic lesion and their correlationPSA level - Bastola, S; Talwar, OP (Journal of Pathology of Nepal, 2014)
Background: The major causes of prostatic enlargement are nodular hyperplasia, prostatitis and neoplasm including prostatic intraepithelial neoplasm. Acidic mucin is absent in benign prostatic glands and is present in some prostatic adenocarcinomas. Mucin stain may be an adjunctive aid in the diagnosis of prostatic adenocarcinoma. This study aims to find out role of acidic mucin in differentiating benign and malignant lesion together with the aid of PSA level. Materials and Methods: A study was done from August 2006 to August 2008. Serum PSA level was performed. Biopsy specimen were processed and stained with Hematoxylin and Eosin as well as Alcian Blue and Periodic Acid Schiff. Data was coded and entered into SPSS v. 11 and Chi-square test and scatter plot was done to analyze the findings. Results: Out of 207 prostatic specimens studied, 78.3% showed BPH with or without prostatitis whereas 12% showed PIN and 8.7% malignancy. PSA density showed statistical significance with p= 0.02, in favor of malignancy. Alcian blue positivity was in 77.8% of malignant cases and 18.5 % in benign cases (p = 0.000003). Acid mucin was more in well differentiating tumours decreasing significantly in high grade malignancies. Combined diagnostic value of PSA>10 ng/ml and Alcian blue positivity showed increase in specificity to 96.8% for diagnosing a malignant lesion, with positive predictive value of 57.1%. Conclusion: PSA density can be used to identify and pick up malignant cases where intermediate levels of PSA values are common. Alcian blue stain can help in assessing the degree of differentiation in malignant cases. <!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3126/jpn.v4i8.11611 Journal of Pathology of Nepal; Vol.4,No8(2014) 612-616